2021
DOI: 10.3389/fpsyt.2021.633880
|View full text |Cite
|
Sign up to set email alerts
|

Brain Arousal as Measured by EEG-Assessment Differs Between Children and Adolescents With Attention-Deficit/Hyperactivity Disorder (ADHD) and Depression

Abstract: Objective: Disturbed regulation of vigilance in the wake state seems to play a key role in the development of mental disorders. It is assumed that hyperactivity in adult ADHD is an attempt to increase a general low vigilance level via external stimulation in order to avoid drowsiness. For depression, the avoidance of stimulation is interpreted as a reaction to a tonic increased vigilance state. Although ADHD is assumed to start during childhood, this vigilance model has been barely tested with children diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…To keep data comparable to prior EEG vigilance research ( 21 , 22 ), we used similar methods for arousal analysis. Consecutive segments of 1-s length were classified into 6 different EEG-vigilance stages: 0, A1, A2, A3, B, and B2/3 (C was not observed), ranging from wakefulness to drowsiness by using the add-on VIGALL 2.1 for BrainVision Analyzer.…”
Section: Methodsmentioning
confidence: 99%
“…To keep data comparable to prior EEG vigilance research ( 21 , 22 ), we used similar methods for arousal analysis. Consecutive segments of 1-s length were classified into 6 different EEG-vigilance stages: 0, A1, A2, A3, B, and B2/3 (C was not observed), ranging from wakefulness to drowsiness by using the add-on VIGALL 2.1 for BrainVision Analyzer.…”
Section: Methodsmentioning
confidence: 99%
“…EEG signals can be divided into different rhythms according to their frequency and amplitude [55], such as delta, theta, alpha, beta, and gamma, which is an effective approach for psychiatric diseases in EEG-related studies [56]. Studies have shown that EEG signals change significantly with increasing levels of depression [57]. Henriques et al [58] collected EEG signals from 15 clinically depressed patients and 13 healthy individuals in resting state with eyes closed and found that the activity in the left frontal lobe of depressed patients was significantly lower than that of healthy individuals.…”
Section: Beta Rhythm Is Significantly Alerted In Ddmentioning
confidence: 99%